Studying the efficacy of giving anthrax toxin as a vaccine intranasally and subcutaneously - H., Al-Zubaidy I.A. (The Iraqi Journal of Veterinary Medicine, 2008)
This study was concerned on the production of Bacillus anthracistoxin and its use as a vaccine. Two groups of guinea pigs wereimmunized with the toxin which was given in a dose of 0.5 mlsubcutaneously to the 1st group while the animals of the 2nd group wereimmunized by instillation in the nose 4 drops into each naris. The twogroups were given booster dose 14 days after the 1st dose. The immunizedand control animals were bled by cardiac puncture 20 days after thebooster dose.In the present study, anthraxin was used as an antigen in EnzymeLinked Immuno Sorbant Assay (ELISA) to measure the optical density(OD) obtained from adminsteration of vaccine in two different routes.High mean of optical density 1.660 ± 0.07 nanometer was recorded tosubcutaneous group and the mean 1.181 ± 0.002 nanometer to theintranasal group.